Reflections of Proto-Austronesian in the Teta Dialect - Utamayana, I Wayan Yoga; I Gede Budasi; Dewa Putu Ramendra (International Journal of Language and Literature, 2024)
This research problem centers on the lexical and phonological forms of Proto Austronesian (PAN) reflected in the Teta Dialect, one of the dialects used by the people of Bima Regency. The Teta dialect has unique linguistic characteristics, but until now there has not been much research to reveal its historical relationship with languages ​​in the Austronesian family, especially in the aspects of sound changes, lexicon and morphology. The aim of this research is to identify sound changes, meaning shifts, and morphological adaptations that occur from the protolanguage to the local dialect.This research is qualitative descriptive research consisting of primary data and secondary data. The subjects of this research are native dialect speakers. The results of this research were analyzed using the theory of sound change, a synthesis of the theories of Crowley, Keraf', and Cser'. This research shows that there are 72 etymones that have a cognate relationship between proto and Teta dialects. The 72 etymones experience 11 types of sound changes, namely; prosthesis (7 etymons), ephenthesis (2 etymons), paragoge (1 etymons), aphaeresis (1 etymons), syncope (4 etymons), apocope (20 etymons), lenition (16 etymons), fortition (13 etymons), metathesis (3 etymons), fusion (1 etymon), and monophthongization (4 etymons). These eleven types of sound changes can be said to be evidence that the Teta dialect is a legacy of Proto Austronesian. In this research, there were 3 informants in Teta village. The limitation of this research was the lack of informants who mastered the vocabulary listed on the word list. In the results of this research, the dialect in Teta village has many similarities to proto-Austronesian. The implications of this research can contribute to the study of Austronesian languages, especially in understanding the pattern of phonological and lexical changes from Proto Austronesian to Teta Dialect. The findings of this research can also be a reference for comparative studies of regional languages ​​in West Nusa Tenggara and the surrounding region.